The totality of the thinkable - Krishnan, M (2023)
This thesis presents four chapters that address the theological and epistemological views of Immanuel Kant. Although each of the four chapters addresses a discrete problem, the chapters are united in their focus on the idea of the ‘totality of the thinkable’ and the related idea of a totality of possible concepts. In particular, this thesis explores the ways in which the totality of the thinkable is implicated in Kant’s criticisms of his German rationalist predecessors.